Artificial Intelligence and Curriculum Prospects: An Assessment of Elementary Schools in Azad Jammu & Kashmir - Aamir Ali Rathore; Syed Jawad Zareen; Adnan Ahmed Rafique, (Dialogue Social Science Review (DSSR), 2025)
The research aims to investigate artificial intelligence and assessment of curriculum prospects for elementary school education. The study focuses on identifying specific areas within curriculum assessment where AI can be incorporated. This important study will explore the assessment of curriculum either AI may be incorporated or not. This study will provide a way forward to all researchers and curriculum developers that how AI can be the part of the curriculum. Descriptive research design and quantitative approach is used and collected data from 70 participants include school leadership and teachers from elementary schools by using convenient sampling. The study shows the broad thoughtful opportunities and challenges associated with AI in elementary education. Results of the study were that majority of the respondents agreed with introducing AI into curriculum which is helpful for the literacy of AI education and curriculum modification continually according to need of modern era. AI can monitor the usefulness of curriculum and identify specific areas and optimize contents teaching methods and facilitate multimodal teaching style to increase the creativity, innovation and problem solving skills. Artificial intelligence education in elementary school curriculum can better train students for 21st century and increase job opportunities for students through AI and technology integration in education.